Three new species of the genus Ranops (Araneae: Zodariidae) from southern Africa - Jocqué, Rudy; Henrard, Arnaud (Zootaxa, 2020)
The genus Ranops Jocqué, 1991 was only known from three species so far. Three new species of the genus are described here: R. robinae sp. nov. (♂♀) from South Africa, R. tharinae sp. nov. (♂♀) from Botswana, and R. wandae sp. nov. (♂♀) from Namibia. Its distribution is discussed and a distribution map for all the Ranops species is provided. Ranops expers (O.P. Cambridge, 1876) does not belong to Ranops and is transferred back to Zodarion Walckenaer, 1826.